New Frontiers in the Pathobiology and Treatment of Cancer Regimen-Related Mucosal Injury - Cinausero, Marika; Aprile, Giuseppe; Ermacora, Paola; Basile, Debora; Vitale, Maria G.; Fanotto, Valentina; Parisi, Giuseppe; Calvetti, Lorenzo; Sonis, Stephen T. (Frontiers in Pharmacology, 2017)
Mucositis is a common complication of chemotherapy, radiotherapy and targeted agents. It often affects compliance to anticancer therapies as it frequently causes schedule delays, interruptions or discontinuations of treatment. Moreover, the economic impact related to the management of mucositis is topical and several estimations of additional hospital costs due to this clinical condition have been recently reported. The ability to determine risk factors for mucositis, to early detect its onset, to assess correctly the degree of this toxicity and to plan its multidisciplinary management are all key elements to guarantee the quality of life of patients and to avoid useless dose reduction or interruption of treatment. The pathogenesis of mucositis is multifactorial and it is classily subdivided into oral and gastrointestinal mucositis according to its anatomic presentation. Treatment and patients’ related factors might help in predicting the frequency and the potential degree of symptoms onset. Here we discuss about clinical presentation and pathogenesis of mucositis in relation to different kinds of treatments. Moreover, we focus on therapeutic and prevention strategies, describing past and present management according to international guidelines and the most promising new data about agents potentially able to further improve the treatment of mucositis in the next future.